Analytical and numerical study on concrete local behavior in thrust phase of TBM-constructed tunnels. - Marum, Tiago Haddad (2022)
Longitudinal cracks are one of the most frequent and severe damages observed in Tunnel Boring Machine (TBM) constructed tunnels. They often appear in the thrust phase as a result of uneven support and load conditions. In order to excavate the soil and advance, the TBM-hydraulic jacks apply high concentrated loads in the last installed ring, which acts as a reaction frame. It generates splitting stresses in the precast segments which might cause those cracks. In addition, steel reinforcements are used to withstand these stresses. Usually, the design of these structural members under jack thrust of TBM are performed based on the finite element method and strut-and-tie theory. The present work aims to discuss the applicability of these models to predict splitting in precast concrete tunnel segments and its comparison with experimental results available in the literature. Considering this purpose, a literature review about experimental tests is made to summarize and comprehend different characteristics tested and to standardize notation evolving material parameters and specimens dimensions. The comparison of the analytical models to predict splitting is carried out by a statistical analysis concerning the difference between models predictions and the experimental results. Also, a numerical modeling approach is used to simulate the effect of reinforcement by discrete fibers on the mechanical local behavior, with a focus on cracking initiation. From the statistical analysis the study suggested two different analytical models with corrections to estimate the load to initiate splitting in concretes. These models with the suggested corrections can be used to design precast segments considering concrete parameters. As for the postcracking behavior, the study concluded that numerical modeling approach adopted was proven useful to evaluate and represent the reinforcement response with sensitivity to variations in fiber content and damage patterns. The results obtained can help to reduce costs related to repair interventions on TBM tunnels construction, once theyre related to ensure a better cracking control in the most critical construction phase of these tunnels, the thrust phase.